Constitutive model of coupled damage-plasticity and its finite element implementation - Ibrahimbegovi´c, Adnan; Markoviˇ, Damijan; Gatuingt, Fabrice (European Journal of Computational Mechanics, 2003)
In this work we present a general theoretical framework for developing a constitutive model capable of coupling two basic types of inelastic behaviour, plasticity and damage. We elaborate upon the main novelty with respect to the previous models of this type, which pertains to a systematic use of criteria for defining the elastic domain, both for plasticity and damage, which can be adapted to a very wide variety of engineering materials, from metals with voids on one side to concrete compaction on the other side. The numerical implementation is first presented for a simple one-dimensional case, and subsequently extended to 2D and 3D criteria which are adequate for either metals or concrete.